Assessing the role of blood glucose levels on intraocular pressure during pre- and postprandial phase in diabetic patients - Pavana Acharya; C. V. Kavitha; P. K. Nayana; K. Sandeep; Rathod Vishakha Narayan; K. S. Anusha (Journal of Clinical Ophthalmology and Research)
Purpose: The purpose of this study was to evaluate the changes in intraocular pressure (IOP) during pre- and postprandial phase of blood glucose estimation and to compare the changes in IOP between well-controlled and uncontrolled diabetics. Subjects and Methods: Three hundred patients with diabetes were assessed for IOP changes in the preprandial phase and postprandial phase. Patients were divided into uncontrolled and controlled diabetes groups based on hemoglobin A1c levels, and IOP changes in pre- and postprandial phase were compared between these two groups. Results: Among 300 patients in our study, the mean age was 63.29 ± 9.88 years. About 41.3% of our study population were males (124 patients), and 58.7% were females (176 patients). Out of 300 patients, 65 (21.7%) patients fall under the uncontrolled diabetes group. The average IOP in preprandial phase was 14.34 ± 2.25, and the average IOP in postprandial phase was 14.88 ± 2.26 (P = 0.001). The average IOP in preprandial phase of well-controlled diabetes group is 14.05, and the average IOP in postprandial phase is 14.48 (P = 0.001). The average IOP in the uncontrolled group in preprandial phase was 15.81, and the average IOP in postprandial phase was 16.37 (P = 0.001). Conclusion: Diabetic patients with uncontrolled diabetes showed significantly raised IOP compared to well-controlled diabetics. There is a statistically significant rise in IOP in postprandial phase of all subjects compared to their preprandial phase. Our study’s inclusion of central corneal thickness-corrected IOP has demonstrated that, in addition to influencing corneal thickness, hyperglycemia also affects aqueous humor dynamics.